2019
DOI: 10.1007/s10745-018-0044-5
|View full text |Cite
|
Sign up to set email alerts
|

Berry Plants and Berry Picking in Inuit Nunangat: Traditions in a Changing Socio-Ecological Landscape

Abstract: Traditional food is central to Inuit culture and sense of identity. Recent changes in lifestyle, climate, and animal populations have influenced how people practice and experience activities on the land. We summarize the findings of 191 new and archived interviews addressing the continued relationships of Inuit to berries in the Canadian territories of Nunavut, Nunavik, and Nunatsiavut. Berry plants have been and remain widely used throughout the study area. Berry picking is an important cultural activity that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 50 publications
0
31
0
Order By: Relevance
“…However, Cuerrier and colleagues also noted limited consensus regarding changes in vegetation and in animal abundance and quality. Research in Kangiqsujuaq has also focused on documenting ice formation and safe snowmobile trails (Tremblay et al, 2006), the availability of berries (Boulanger‐Lapointe et al, 2019) and changes in sea ice thickness (Dufour‐Beauséjour et al, 2018). The long‐term environmental and socioeconomic impacts of mining activities in the region is also a subject of concern (Duhaime, Bernard, & Comtois, 2005; Rodon & Lévesque, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…However, Cuerrier and colleagues also noted limited consensus regarding changes in vegetation and in animal abundance and quality. Research in Kangiqsujuaq has also focused on documenting ice formation and safe snowmobile trails (Tremblay et al, 2006), the availability of berries (Boulanger‐Lapointe et al, 2019) and changes in sea ice thickness (Dufour‐Beauséjour et al, 2018). The long‐term environmental and socioeconomic impacts of mining activities in the region is also a subject of concern (Duhaime, Bernard, & Comtois, 2005; Rodon & Lévesque, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…In boreal and Arctic communities, the harvesting of wild plants, particularly wild berries, contributes significantly to a subsistence diet (Thornton, 1998;Hupp et al, 2015;Boulanger-Lapointe et al, 2019). In the Arctic, where terrestrial non-native plant spread remains small relative to other regions (Wasowicz et al, 2020), communities are increasingly implementing prevention and control measures to protect important wild berry harvesting areas (Spellman and Swenson, 2012;Leask and Winter, 2017).…”
Section: Variation In Invasive Plant Phenologymentioning
confidence: 99%
“…We have already made reference above to Mātauranga Māori (Ataria et al 2018, Makey and Awatere 2018, Wehi et al 2019 a , 2019 b ) as one cohesive Indigenous worldview that includes knowledge system structure and function associated with the Indigenous Nations of Aotearoa ‐New Zealand. In a recent knowledge synthesis report, Levac et al (2018) identified and provided a brief overview of other prominent knowledge system models that are grounded within Indigenous ways of knowing, including but not limited to Kaswentha , Two‐Row Wampum, and Haudenosaunee knowledge management (Ransom and Ettenger 2001, Whitlow et al 2019, Barnhill‐Dilling et al 2020); Anishinaabe Minobimaadiziwin , Good Life (Debassige 2010, Chiblow 2019, Awāsis 2020); Inuit Qaujimajatuqangit (Chanteloup et al 2018, Boulanger‐Lapointe et al 2019, Wiseman and Kreuger 2019); Medicine Wheel learning and teaching (LaFever 2016, Marchand et al 2020), Etuaptmumk , Two‐Eyed Seeing, from the Mi'kmaw Nation (Bartlett et al 2012, Martin et al 2017, Rowett 2018); and Ubuntuism (Chemhuru 2019, Gwaravanda 2019). Recently, there has been a global explosion in scholarship focusing on the role of Indigenous knowledge systems in ecology and natural resource management.…”
Section: Indigenous Scholarship Regarding Knowledge Systemsmentioning
confidence: 99%